Development of a Location-Based Augmented Reality Application for Navigation - Edson Yahuda Putra, M.Kom; Andria Wahyudi; Privan Nabut; Aaron Pelle (CogITo Smart Journal, 2024)
Universitas Klabat (UNKLAB) is one of the private higher education institutions directly affiliated with the Seventh-day Adventist Church (SDA), located in North Minahasa, North Sulawesi. UNKLAB has approximately 3,500 students and boasts many buildings and facilities, including lecture halls, dormitories, sports fields, and more. Given the vast campus and numerous buildings, navigation is essential to help individuals find their way to specific buildings or locations. With the advancement of technology, the author identified an opportunity to implement Augmented Reality (AR) technology as a navigation aid at Universitas Klabat, utilizing iOS as the chosen platform. In this application, users can search for various locations, such as buildings, facilities, or faculty residences. The Research and Design (R&D) method was employed for this study, wherein the researcher conducted investigations and subsequently developed this application. During the application's development, one of the models within the Software Development Life Cycle (SDLC), namely the Prototyping model, was utilized. The researcher successfully created a location-based Augmented Reality application for navigating UNKLAB's campus, and it functions effectively on iOS mobile devices.